Praktik Pembelajaran Tematik di Sekolah Dasar Dengan Pendekatan Sosiologi - Rusfadia Saktiyanti Jahja; dan Devi Septiandini (Laboratorium Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2017)
The aim of this study explaining about application of thematic learning in primary schools and to what extent it can increase students' motivation. Results of studies conducted show that, although it turns out the rules of the mandatory use is conducted a thematic integrated learning model compulsory for all schools, but not all schools do it. The reason why schools do not want to implement it because considering the difficulties to set up the learning media. furthermore, the system of assessment and evaluation system provided is still not integrated also. Teachers still using separated learning. There has been no comprehensive training on the implementation of this thematic models, moreover the facilities and infrastructure that do not support the learning process.